Responsabilidade social: a empresa sob o prisma da ética - Cavalcante, Wellington Rone de Siqueira (2019)
This paper aims to observe the social responsibility of the company seeking, initially, the analysis of the company, its possible definition, passing by its profit objective with its beneficial effects on the community, as well as its social function, and importance in the society. Then, we analyze business ethics, focusing on the conduct of companies, drawing a parallel between ethics and morality to verify their importance in society. Finally, we analyze the company's attitude, its social and environmental responsibility, and with the individual in general. Thus, a possible relationship is sought between social responsibility and ethics. The approach of the present research proposes a social responsibility based on business ethics, ensuring a healthy environment for the present and future generations as provided by the current Federal Constitution and, therefore, a company conduct that serves as a paradigm before society. as a whole. It uses the hypothetical-deductive method as well as bibliographic research.